The property tax and local autonomy - Bell, Michael E. (Lincoln Institute of Land Policy, 2025)
The property tax and local autonomy : an overview / Michael E. Bell and David Brunori -- Local government : an economic perspective / Wallace E. Oates -- The median voter and school-finance reform : how tax-base sharing undermines the efficiency of the property tax / William A. Fischel -- Comparing local autonomy across states / Harold Wolman, Robert McManmon, Michael E. Bell, and David Brunori ; commentary Carol Weissert -- Are state and local finances becoming more or less decentralized and should we care? / Katrina Connolly, David Brunori, and Michael E. Bell ; commentary Tim Conlan -- An overview of the implications of eliminating the property tax : what do recent state debates and prior state experience tell us? / Ronald C. Fisher, Andrew Bristle, and Anupama Prasad ; commentary David Sjoquist -- What will the future of the property tax look like and what will take its place? / Richard F. Dye ; commentary David Brunori -- States and fiscal policy space of cities / Michael A. Pagano and Christopher W. Hoene ; commentary Andrew Reschovsky.